Regulatory Effects of HMG CoA Reductase Inhibitor and Fish Oils on Apolipoprotein B-100 Kinetics in Insulin-Resistant Obese Male Subjects With Dyslipidemia - Chan, Dick C.; Watts, Gerald F.; Barrett, P. Hugh R.; Beilin, Lawrence J.; Redgrave, Trevor G.; Mori, Trevor A. (Diabetes (New York, N.Y.), 2002)
Regulatory Effects of HMG CoA Reductase Inhibitor and Fish Oils on Apolipoprotein B-100 Kinetics in Insulin-Resistant Obese Male Subjects With Dyslipidemia Dick C. Chan 1 , Gerald F. Watts 1 , P. Hugh R. Barrett 1 , Lawrence J. Beilin 1 , Trevor G. Redgrave 2 and Trevor A. Mori 1 1 Department of Medicine, University of Western Australia and the Western Australian Institute for Medical Research, Crawley, Western Australia 2 Department of Physiology, University of Western Australia, Crawley, Western Australia Abstract Hepatic accumulation of lipid substrates perturbs apolipoproteinB-100 (apoB) metabolism in insulin-resistant, obese subjects and may account for increased risk of cardiovascular disease. In a placebo-controlled trial, we examined the independent and combined effects of decreasing cholesterol synthesis with atorvastatin (40 mg/day) and triglyceride synthesis with fish oils (4 g/day) on apoB kinetics. The subjects were 48 viscerally obese, insulin-resistant men with dyslipidemia who were studied in a fasted state. We found that atorvastatin significantly decreased plasma apoB-containing lipoproteins ( P < 0.001, main effect) through increases in the fractional catabolic rate (FCR) of VLDL-, IDL-, and LDL-apoB ( P < 0.01). Fish oils significantly decreased plasma levels of triglycerides and VLDL-apoB ( P < 0.001), decreased the VLDL-apoB secretion rate ( P < 0.01), but increased the conversion of VLDL to LDL ( P < 0.001). Compared with placebo, combined treatment with atorvastatin and fish oils decreased VLDL-apoB secretion ( P < 0.03) and increased the FCR of apoB in each lipoprotein fraction ( P < 0.03) and the percent conversion of VLDL to LDL ( P < 0.05). None of the treatments altered insulin resistance. In conclusion, in visceral obesity, atorvastatin increased hepatic clearance of all apoB-containing lipoproteins, whereas fish oils decreased hepatic secretion of VLDL-apoB. The differential effects of atorvastatin and fish oils on apoB kinetics support their combined use in correcting defective apoB metabolism in obese, insulin-resistant subjects. Footnotes Address correspondence and reprint requests to Prof. G.F. Watts, Department of Medicine, University of Western Australia, GPO Box X2213, Perth, Western Australia 6847. E-mail: gfwattsatcyllene.uwa.edu.au . Received for publication 18 March 2002 and accepted in revised form 3 May 2002. apo, apolipoprotein; apoB, apolipoprotein B-100; CVD, cardiovascular disease; DHA, docosahexaenoic acid; EPA, eicosapentaenoic acid; FCR, fractional catabolic rate; GLM, general linear model; HOMA, homeostasis model assessment; IDL, intermediate-density lipoprotein; NEFA, nonesterified fatty acid; PPAR, peroxisome proliferator-activated receptor; RLP, remnant-like particle; SREBP-1c, sterol regulatory element binding protein-1c. DIABETES